The effectiveness of music therapy in nursing practices in patients with Alzheimer a narrative review (Research, Society and Development, 2022)
This article presents the study on the effectiveness of music therapy in nursing practices in patients with Alzheimer's disease, a chronic and degenerative pathology that compromises cognitive functions, leading to neuropsychiatric disorders, as well as changes in behavior and how music therapy can improve patients' quality of life. The objective is to describe music therapy, with therapeutic purposes and health treatments, since the execution of these practices also provides a non-verbal articulation of the patient and thus, will facilitate the expression of this in different situations It is a narrative review study, it is characterized as descriptive with a qualitative approach, which is a type of research by review. Data collection was carried out on the platforms Scientific electronic library (Scielo), Latin American and Caribbean Literature on Health Sciences (Lilacs), U.S. National Library of Medicine (PubMed), Virtual Health Library (Bvsalud), using the descriptors: efficacy, music therapy, nursing, and Alzheimer's. The results show that the effect that music brings enables the nurse to meet the client and stimulates the communication process, inciting the expression of different emotions, self-perception and reflection on what has been experienced. Also referenced in the philosophical assumptions of palliative care, communication, an essential attribute of interpersonal relationships, must be empathetic and compassionate, provide support and sustenance in the end of life, express messages that denote attention and care with words and attitudes.